Natural convection of fluid with variable viscosity and viscous dissipation from a heated vertical wavy surface in presence of magnetic field - Parveen, Nazma; Alim, M. A. (Journal of Naval Architecture and Marine Engineering, 2020)
ABSTRACT The present numerical work describes the effect of the temperature dependent variable viscosity and viscous dissipation on natural convection heat transfer boundary layer flow of a viscous incompressible electrically conducting fluid along a vertical wavy surface in presence of a transverse magnetic field. The wavy surface is maintained at uniform wall temperature that is higher than that of the ambient. A simple coordinate transformation is employed to transform the wavy surface into a flat plate. A marching finite difference scheme is used for present analysis. The numerical results, including the developments of the skin friction coefficients, the local Nusselt number, the streamlines as well as the isotherms are presented and discussed in detail. The results of this investigation illustrated that the skin friction coefficient increase with an increase of the variable viscosity and viscous dissipation parameter, while the local Nusselt number at the heated surface decrease with increasing values of variable viscosity, intensity of magnetic field and viscous dissipation parameter.